KESIAPAN UNTUK BERUBAH KARYAWAN DIVISI HR PT. X STUDI KASUS PROSES DESENTRALISASI SISTEM ERP/SAP MODUL ORGANIZATION MANAGEMENT (OM) - Dea Franceline; Rayini Dahesihsari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2015)
Change in technology is one among the most frequent change happened in an organization. PT. X now is dealing with technology change by taking a decentralization of SAP management of its business units. This changing is done due to the lack of effectiveness of centralized management, which result on delay in delivery the services. Socializations, trainings, and intensive coaching are conducted to manage the change. The purpose of this research is to describe HR unit employees’ change readiness in PT. X, in regards of the decentralization process of ERP/ SAP module Organization Management (OM).This is a quantitative research. The participants are 41 people HR unit employees in PT. X who responsible of SAP management. The measurement is Readiness for Organizational Change (ROC. The data are analysed using descriptive statistics. The result shows that generally, the HR unit employees’ readiness towards the implementation of SAP OM module in each unit is categorized as moderate level with the lowest readiness on the “management support” dimension. The business unit of SHM has low “personal valence” dimension. Hence, the intervention program focuses to improve the management support dimension by proposing a monitoring program, while to improve personal valence dimension in particular on the SHM business unit by creating survey feedback.